2010
DOI: 10.1155/2010/958213
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Sutured Tie-Over Dressings on the Nasal Dorsum

Abstract: The nose is a common site for basal and squamous cell carcinomas. Surgical excision can leave a defect that is appropriate for reconstruction with full thickness skin grafting. Tie-over dressings have gained popularity in this setting. We propose that steri-strips alone provide the necessary support to facilitate excellent graft take.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Fifteen articles met the inclusion criteria involving only skin surgery (for details see Table S1, Supplemental Digital Content 4, http://links.lww.com/DSS/A423. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Three studies used randomization, [28][29][30] and 4 studies compared a no tie-over dressing with a tie-over dressing but did not always specify the materials used for the bolster. 27,29,31,33 Two articles mentioned both STSGs and FTSGs and did not subdivide the graft take per technique.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen articles met the inclusion criteria involving only skin surgery (for details see Table S1, Supplemental Digital Content 4, http://links.lww.com/DSS/A423. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Three studies used randomization, [28][29][30] and 4 studies compared a no tie-over dressing with a tie-over dressing but did not always specify the materials used for the bolster. 27,29,31,33 Two articles mentioned both STSGs and FTSGs and did not subdivide the graft take per technique.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,38 Thirteen studies used only FTSGs. [25][26][27][29][30][31][32][33][34][35][36][37]39 The graft defect size was described in different measurements of length (mm and cm) or surface area (mm 2 and cm 2 ) and varied from 8 mm in length (smallest) 34 to 52.4 cm 2 (largest area). 25 Nine studies reported the use of additional antibiotics: systemic 35 and local.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations